2005
DOI: 10.1038/sj.onc.1208777
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional silencing of secreted frizzled related protein 1 (SFRP1) by promoter hypermethylation in non-small-cell lung cancer

Abstract: Secreted frizzled related protein 1 (SFRP1) is an antagonist of the transmembrane frizzled receptor, a component of the Wnt signaling pathway, and has been suggested to be a candidate tumor suppressor in several human malignancies. Since SFRP1 is located at chromosome 8p11, where lung cancers also exhibit frequent allelic loss, we hypothesized that the inactivation of SFRP1 is also involved in lung carcinogenesis. To substantiate this, we performed mutational analysis of SFRP1 for 29 nonsmall-cell lung cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
116
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 153 publications
(122 citation statements)
references
References 23 publications
6
116
0
Order By: Relevance
“…Because none of the breast cancer cell lines presented aberrant TCF/LEF transcription, we used an expression vector encoding a b-catenin mutant to boost Wnt signalling. We found that the TCF/LEF transcriptional activity induced by the mutant b-catenin was synergistically upregulated when combined with SFRP1 depletion, which is consistent with the recent observation by Fukui et al (2005). Using non-small-cell lung carcinoma cells in which SFRP1 was methylated, they showed that when SFRP1 was cotransfected with mutant b-catenin, SFRP1 could attenuate TCF/LEF activity induced by exogenous b-catenin.…”
Section: Genetics and Genomicssupporting
confidence: 91%
See 2 more Smart Citations
“…Because none of the breast cancer cell lines presented aberrant TCF/LEF transcription, we used an expression vector encoding a b-catenin mutant to boost Wnt signalling. We found that the TCF/LEF transcriptional activity induced by the mutant b-catenin was synergistically upregulated when combined with SFRP1 depletion, which is consistent with the recent observation by Fukui et al (2005). Using non-small-cell lung carcinoma cells in which SFRP1 was methylated, they showed that when SFRP1 was cotransfected with mutant b-catenin, SFRP1 could attenuate TCF/LEF activity induced by exogenous b-catenin.…”
Section: Genetics and Genomicssupporting
confidence: 91%
“…Consistent with that idea, we have previously found that SFRP1 is methylated in several breast cancer cell lines (Suzuki et al, 2002), and two other groups recently reported frequent SFRP1 methylation in both primary and cultured breast cancer cells (Lo et al, 2006;Veeck et al, 2006). To date, epigenetic silencing of SFRP1 has been identified in a variety of malignancies, including cancers of the bladder (Stoehr et al, 2004), prostate (Lodygin et al, 2005), lung (Fukui et al, 2005) and breast, although abnormalities involving other SFRP family genes are largely unexplored.We previously showed that SFRP1, SFRP2 and SFRP5 are frequently inactivated in CRC and gastric cancer (GC) (Suzuki et al, 2002;Nojima et al, 2007), and that SFRPs suppress constitutive Wnt signalling when overexpressed in CRC and GC cells. Similarly, Bafico et al (2004) reported that constitutive Wnt signalling could be suppressed in breast cancer cells by SFRP1 and DKK1.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…Interestingly, sFRP1 functions as a negative regulator of the Wnt pathway and blocks the activation of the downstream target genes (Kawano and Kypta, 2003). Downregulation of the sFRP1 has been found in a variety of malignancies including colon (Caldwell et al, 2004), breast (Veeck et al, 2006), bladder (Stoehr et al, 2004), ovarian (Takada et al, 2004), and lung (Fukui et al, 2005) cancers. It has been reported that reconstitution of sFRP1 inhibits HCC growth in vitro and in vivo, and the sFRP1 restoration offers a potential therapeutic approach for treatment of HCC (Hu et al, 2009;Jiang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Decrease in the sFRP1 expression due to promoter hypermethylation may result in the activation of the Wnt pathway and consequent tumor development. Interestingly, reduced expression of sFRP1 has been found in many malignancies, including colorectal (Caldwell et al, 2004;Suzuki et al, 2004), lung (Fukui et al, 2005), ovarian (Takada et al, 2004), breast (Veeck et al, 2006), esophageal (Zou et al, 2005;Clement et al, 2006), and liver (Shih et al, 2006) cancers.…”
mentioning
confidence: 99%